CHEMICAL COMPOSITION OF SOIL AND THEIR RELATIONSHIP WITH AGROECOLOGICAL FACTORS - Sotiboldieva Gozalkhan Tolibjonovna; Mominova Ogylcha Makhmud daughter (Innovate Conferences, 2025)
This article investigates the chemical composition of soils and their relationship with agroecological factors in the conditions of the Fergana Valley. The study analyzed key macroelements — nitrogen (N), phosphorus (P₂O₅), potassium (K₂O), calcium (Ca), and magnesium (Mg) — as well as microelements such as iron (Fe), zinc (Zn), and copper (Cu). The results show that the chemical composition of the soil is directly influenced by climate, salinity, moisture, and fertilization systems. Nitrogen and phosphorus levels increase with moisture, while salinity reduces the balance of potassium and magnesium. The decline of organic matter in the soil slows down the natural nutrient cycle. Based on the findings, practical recommendations were developed to maintain soil chemical balance and improve fertility under agroecological conditions.
Keywords: soil chemical composition, nitrogen, phosphorus, potassium, agroecological factors, salinity, organic matter, Fergana Valley.